Knowledge sharing model for facilities management of private finance initiative projects performance / Irwan Mohammad Ali - Mohammad Ali, Irwan (2019)
An effective approach for knowledge retention within the Private Finance Initiative (PFI) project during the Facilities Management (FM) stage has become a flourishing and critical concern. The presence and development of several Higher Learning Institutions (HLI) that implement the PFI scheme encounter many issues and problems, particularly at the FM stage. Through group brainstorming, it shows that the performance problems are explicitly related to the knowledge issues. It is not easy to manage problems associated with the performance management of the FM-PFI project. Therefore, an effective initiative must be executed to ensure that the performance of FM-PFI projects is reflected as in the contract. Previous studies show that Knowledge Sharing (KS) has significant influences on organisation performance. Hence, this research suggests that the implementation of effective KS has the potential in improving the performance management of FM-PFI projects. The research aim is to propose a KS model that can improve FM of the PFI projects performance. Therefore, the first research objective is to identify the determinant factors for KS in improving FM of the PFI projects performance. The second research objective is to examine the relationship between the identified determinant factors with KS towards performance management of FM of the PFI projects.